2019
DOI: 10.1186/s12913-018-3853-8
|View full text |Cite
|
Sign up to set email alerts
|

Brief telephone counselling is effective for caregivers who do not experience any major life events – caregiver-related outcomes of the German day-care study

Abstract: BackgroundTo date, there has been a dearth of scientifically tested, established intervention concepts focussed on supporting informal caregivers and embedded in routine health care structures. The aim of this study was to assess effects of a brief telephone intervention for caregivers of persons with cognitive impairment (PCIs) on caregivers’ depressiveness and subjective burden.MethodsA two-arm cluster-randomised controlled intervention study was carried out at 32 German day-care centres. During the six-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…For detailed reasons for the dropout and the distributions of the dropouts in the control and intervention groups between baseline and the 6-month follow-up, see Behrndt el al. [18]. Three hundred four dyads could be included in the analysis of the follow-up data after 12 months (t2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For detailed reasons for the dropout and the distributions of the dropouts in the control and intervention groups between baseline and the 6-month follow-up, see Behrndt el al. [18]. Three hundred four dyads could be included in the analysis of the follow-up data after 12 months (t2).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, an outreach telephone counseling intervention for their caregivers was carried out, and both were analyzed for their efficacy. The DeTaMAKS short-term effects were published [15, 16]. However, it is not yet clear whether the German day-care study interventions have long-term effects, and if so, for which aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies found the interventions to be effective (e.g., [ 23 , 24 , 25 , 26 ]), others found no significant difference between the intervention and control groups (e.g., [ 27 , 28 , 29 , 30 ]). Still, others found partial support for the telephone interventions that were limited to certain subgroups of caregivers (e.g., [ 31 , 32 ]) or at certain follow-up points (e.g., [ 33 , 34 , 35 , 36 ]) regarding depressive symptoms. However, some studies had significant results in other outcomes, such as a high percentage of complete or partial attainment [ 33 ], an improvement in well-being [ 34 , 35 , 36 ], coping with the care situation [ 34 , 36 ], perceived health [ 34 ], physical health [ 35 , 36 ], quality of life [ 35 ], the behavior of the care recipient [ 36 ], and a reduction in physical complaints [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results for reported depressive symptoms of these long-term evaluations were not very encouraging. Donath et al [ 39 ] analyzed the long term data of the cluster-randomized controlled trial by Berhndt et al [ 32 ] in which 453 caregivers received a telephone advice intervention ( n = 263) or usual care ( n = 190). There were no significant differences between the two groups at the 12-month follow-up, although secondary analyses found a moderate effect size (Cohen’s d = 0.52) for caregivers of people with mild dementia.…”
Section: Introductionmentioning
confidence: 99%